THE ROLE OF NAPS AND DAYTIME SLEEPINESS IN STROKE RISK: A REVIEW OF THE LITERATURE FROM A PUBLIC HEALTH AND SLEEP-MONITORING TECHNOLOGY PERSPECTIVE - Maria Nowakowska; Oliwia Jerzyńska; Miszela Kałachurska; Martyna Rożek; Aleksandra Kowalewska-Kurek; Aleksandra Lisowska; Bartosz Nowak; Maria Sierant; Mateusz Gural; Constancia Esther Guy (International Journal of Innovative Technologies in Social Science, 2026)
The aim of this review is to summarize the literature on daytime naps and their duration in relation to stroke risk, with particular emphasis on physiological mechanisms, demographic factors, and lifestyle. Analysis has shown that short naps of up to 30 minutes improve cognitive functions, blood pressure regulation, and stress hormone levels, and thus may have not only a neutral but also a beneficial effect on the human body. In contrast, long naps lasting 60–90 minutes or repeated multiple times during the day appear to significantly increase the risk of stroke, especially in older individuals with comorbidities such as diabetes, obesity, or hypertension. The mechanisms linking naps to stroke risk include changes in the autonomic nervous system, blood pressure, inflammatory status, and blood–brain barrier integrity. The authors emphasize that both nighttime sleep and daytime naps can be monitored for duration and quality using modern, widely available devices, such as wrist-worn trackers or mattress-embedded sensors, allowing objective assessment of sleep patterns and early identification of stroke risk factors. Further research is needed to develop systems for early detection of abnormal sleep and nap patterns, which could serve as a basis for implementing personalized stroke prevention strategies.